Cirebon City Police Law Enforcement Against Online Gambling Affiliators - Izaz, Rofiq Khoirul; Maulana, Gibran; Saputra, Jovian; Ismayana, Ismayana; Nurhaqi, Ari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine and analyze the form of law enforcement carried out by Cirebon City Police against online gambling affiliators that are increasingly widespread in the digital era. The method used in this research is an empirical juridical approach, with data obtained through literature studies and direct interviews with law enforcement officials. The results show that law enforcement against online gambling affiliators faces various challenges, including limited regulations that specifically regulate affiliator activities, tracking difficulties due to the use of sophisticated digital technology, and lack of public awareness of the legal impact of these activities. Nevertheless, Cirebon City Police has taken various preventive and repressive measures, including digital forensic-based investigations and cooperation with related institutions. These law enforcement efforts need to be supported by updating legal policies that are adaptive to the dynamics of cybercrime and increasing the capacity of the apparatus in dealing with technology-based crimes.